Effect of heating rate and temperature on microstructure evolution of cold rolled dual phase steel. (September 2014) - Meng, Q.; Li, J.; Li, P.
<x content-type="archive" xml:space="preserve">Abstract</x> Microstructural evolution of a dual phase steel sheet at different heating rates and temperatures was investigated by scanning electron microscopy (SEM). Texture, grain size distribution and grain boundary characteristic of ferrite phase in the dual phase steel were analysed by the electron backscattered diffraction (EBSD) technique. EBSD results show that the sample had obvious 111//ND (normal direction) and 001 //ND texture at the heating rate of 50 and 250 K s−1 respectively, and that the grain size may be refined by rapid annealing. However, the effect of the heating rate on microstructure decreases as the heating temperature reaches 1173 K. It was found that grain size distribution and grain boundary characteristics of dual phase steel have been significantly affected by heating rate and temperature.